Theoretical and experimental studies on the self‐healing properties of metallised capacitor films under multiple stresses - Zhiyuan Wu; Shangshu Liu; Tong Tong; Shaolong Zhong; Jiantao Wang; Hongbin Qi; Zhimin Dang; Wei Wang (High Voltage)
Abstract Metallised film capacitors, for the most important merits is the excellent self‐healing property, have significant electrical insulation advantage. The essential factors affecting the self‐healing properties of metallised polypropylene film capacitors (MPPFCs) are first analysed, and a self‐healing performance characterisation test platform for metallised polypropylene capacitor films was built. Both the voltage/current waveforms and discharge patterns of the self‐healing process under multiple stresses including temperature, voltage and inter‐layer pressure were recorded and discussed. The correlation between self‐healing performance characterisation and the carbon that appeared on the surface of the dielectric layer during the arc extinction time is clarified. Finally, by virtue of an equivalent dynamic circuit model, the influence of square resistance and the equivalent capacitance of the power grid on self‐healing has been theoretically studied.